Withaferin A and its Derivatives as Potential Anti-cancer Drug Lead Candidates: An In-silico Drug Design (Dhaka University Journal of Pharmaceutical Sciences, 2025)
The aim of the research is to identify novel bioactive molecules to treat breast and lung cancer, specifically natural Withaferin A and its structural analogues, utilizing the most advanced and reliable in-silico drug design methodologies. At the starting point of this work, the biological pass prediction score was computed to identify the target protein. The probability of the active (Pa) score is superior in antineoplastic agents (Pa: 0.916–0.942) compared to antifungal (Pa: 0.474–0.795) and antibacterial agents (Pa: 0.260–0.598). Consequently, oncogenic proteins associated with breast and lung cancer were identified, and the in-silico analysis proceeded. The docking scores of investigational medicines ranged from -7.3 to -7.8 kcal/mol for breast cancer-targeted protein PDB: 2W96 and from -7.4 to -8.4 kcal/mol for PDB: 4DNL. Conversely, the docking scores for regular palbociclib and tamoxifen were -7.8 kcal/mol and -8.4 kcal/mol, respectively. The docking scores of investigational drugs ranged from -7.6 to -9.2 kcal/mol for lung cancer-targeted protein PDB: 2IVS and from -8.5 to -9.8 kcal/mol for PDB: 3L9P. The docking scores for conventional Pralsetinib and Crizotinib were -9.4 kcal/mol and -8.9 kcal/mol, respectively. The docking score is critically significant, indicating that Withaferin A derivatives have superior docking scores to conventional chemotherapeutic drugs for breast and lung cancer. This experiment successfully assessed drug-likeness, ADME, and toxicity prediction, revealing that all compounds exhibited excellent human intestinal absorption, moderate solubility in aqueous medium, and were utterly free of hepatotoxicity and skin sensitization. Consequently, based on computational analysis, we believe that natural Withaferin A derivatives may serve as superior inhibitors in treating breast and lung cancer, warranting further experimental research.Dhaka Univ. J. Pharm. Sci. 24(1): 105-120, 2025 (June)